Penerapan Nilai-Nilai Islam dalam Berwirausaha pada Masyarakat di Ris One Bakery Desa Bandar Setia Tembung - Muhammad Tohri; Nurhanifah Nurhanifah (Fakultas Syariah IAIN Laa Roiba Bogor, 2024)
This research uses a phenomenological approach. The researcher uses a phenomenological approach in conducting this research. In simple terms, phenomenology is part of a qualitative methodology, with the title Application of Islamic Values ​​in Entrepreneurship in the Community at Ris One Bakery, Bandar Setia Tembung Village. The company is run with reference to Islamic values ​​where apart from gaining world profits, this company also does not exclude provisions for the afterlife. For example, when it comes to prayer time, all employees are required to join in congregational prayers, both midday prayers and Asr prayers, which are performed after all work is finished or before home time and if there is overtime, the prayers are performed alternately. Facilities and guidance are provided to improve employees' ability to read the Al-Qur'an by bringing in TPQ teachers which are conducted twice a week during break times. Employees are also facilitated in taking part in event programs held by the center, namely MESM (Mayangkara Spiritual Emotional Management) and there are also studies carried out in the Mayangkara employee chat group, employees who reply to these studies will later be recorded and given points and rewards.